1997
DOI: 10.1136/emj.14.1.52
|View full text |Cite
|
Sign up to set email alerts
|

Necrotising fasciitis as a complication of steroid injection.

Abstract: Necrotising fasciitis is described as a complication of steroid injection of a painful shoulder in a previously well female. This case highlights a very rare life threatening emergency after steroid

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 12 publications
1
13
0
1
Order By: Relevance
“…Whereas streptococci are common bacterias responsible for many uncomplicated wound infections, spreading streptococcal infections causing a state of toxic shock within a short period of time are being reported with increasing frequency. Such situations are not only encountered after trauma [16], injections [4] or orthopedic operations [12,23], they are also found complicating nasopharyngeal infections [6] and in pediatrics [17]. Moses et al [17] have demonstrated an increasing frequency of these infections in pediatric patients during the last decade, a phenomenon which has also been reported for other patient cohorts [26].…”
Section: Introductionmentioning
confidence: 70%
“…Whereas streptococci are common bacterias responsible for many uncomplicated wound infections, spreading streptococcal infections causing a state of toxic shock within a short period of time are being reported with increasing frequency. Such situations are not only encountered after trauma [16], injections [4] or orthopedic operations [12,23], they are also found complicating nasopharyngeal infections [6] and in pediatrics [17]. Moses et al [17] have demonstrated an increasing frequency of these infections in pediatric patients during the last decade, a phenomenon which has also been reported for other patient cohorts [26].…”
Section: Introductionmentioning
confidence: 70%
“…7 Birkinshaw et al reported NF at the shoulder region as a complication of steroid injection of a painful shoulder in a previously healthy female. 8 Necrotizing fasciitis with myonecrosis has not been reported in children as a complication of routine vaccination or injection. However, minor trauma and small punctures are known causes of NF in children.…”
Section: Discussionmentioning
confidence: 99%
“…Initiating steroids was a therapeutic dilemma, as steroid use has been reported as an aetiological factor in necrotising fasciitis. 9,10 This was a unique case, which presented with fatal vasculitis resulting in tissue necrosis amounting to necrotising fasciitis and posing a therapeutic dilemma about role of systemic steroids.…”
Section: Managementmentioning
confidence: 99%